Convergence of Religion and Positive Psychology, Growth Mindset in Islamic Religious Studies - Arifudin, Moch.; Ramadhan, Idang; Nurjanah, Fitri; Prihantono, Muhamad Rifqi; Subhan, Nurul Izzah (Proceeding International Conference on Religion, Science and Education, 2025)
A growth mindset is a positive psychology concept that discusses the mindset and how a person views their abilities. The term growth mindset only emerged and was first introduced by Dweck in the early 21st century. However, long before that, the concept of a growth mindset had long been introduced in Islamic religious studies, both implied in the Qur'an, hadith, and ancient books written by Islamic scholars of the past such as Imam al Ghazali. The topic of growth mindset in Islamic religious studies is interesting to study considering the rich literature of Islamic religious studies that has existed since ancient times. This study explores the concept of a growth mindset in Islamic religious studies. This study uses a library research method, namely collecting data through studies and understanding theories from various literature such as books, journals, and previous research relevant to the research topic. Data were collected by searching for and filtering literature related to the growth mindset in Islamic religious studies. The collected data were then analyzed critically to find patterns, relationships, and implications to achieve a comprehensive understanding of the growth mindset in Islamic religious studies. The results of the study show that in Islamic religious studies, the concept of a growth mindset is explained in various ways, such as teachings about the importance of self-development but still does not eliminate the role of God in the process. A growth mindset sees failure as an opportunity to learn and improve oneself, in line with Islamic teachings that emphasize the importance of effort, patience, and lifelong learning. This study is expected to revive Islamic religious thoughts and studies in the global scientific realm. In this regard, research on the convergence of Islam and positive psychology needs to be done a lot.